(untitled) (Journal of Geography and Environmental Management, 2016)
In article the ecological and economical and geographical assessment on the basis of the analysis of a condition of the polluted lands within territories of the old mastered oil and gas fields in Apsheronsk the economic region of Azerbaijan was carried out. Geographical distribution near the polluted lands, their forms, typological classification, the optimum directions and types of recultivation of the polluted lands was defined.